Review Artikel: Inovasi Keramik Berbasis Organosilikon: Polymer-Derived Ceramics (PDCs) - Savitri, Afridha Cita; Wati, Laely Septiya; Nanda, Nanda; Nurliani, Navila; Anggraeni, Maya Erliza; Pasaribu, Marvin Horale (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
Innovation and modern methods in ceramic production, as a transition from conventional/traditional methods, are needed to improve production efficiency and quality. One innovation in the ceramic industry is the polymer-derived ceramic (PDC) technology with the utilization of organosilicon compounds. PDCs are ceramics derived from preceramic organosilicon polymer precursors, which are generally divided into polysiloxane, polycarbosiloxane, polycarbosilane, polysilycarbodimiides, polysilazane, polyborosilazanes, polyborosilanes, and polyborosiloxanes. The transformation of organosilicon polymers into ceramics is carried out through four stages: shaping, cross-linking, pyrolysis, and ceramization. PDCs have high-temperature resistance properties, making them suitable for various applications in extreme environments. The forms of PDC applications are as semiconductors, sensors, coating/membranes, and fibers.